2021
DOI: 10.3390/biology10070596
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Stem Cell Progeny by Probiotics during Regeneration of Gastric Mucosal Erosions

Abstract: Patients with gastric mucosal erosions are predisposed to chronic gastritis, ulcer or even cancer. The repair of mucosal erosions involves several events including proliferation of gastric epithelial stem cells. The aim of this study was to investigate the effects of the probiotic mixture of De Simone Formulation on gastric epithelial stem cell lineages in mouse models of gastric mucosal erosions. Gastric erosions were induced by a single oral gavage of 80% ethanol containing 15 mg/mL acetylsalicylic acid (5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…18 Athiyyah's study showed that L. plantarum IS-10506 activates ISCs for inflammation mitigation, 19 while combined probiotic therapy has been effective in treating stomach erosions by modulating stem and secretory cell lineages. 20 Furthermore, dietary raffinose supports Lactobacillus reuteri in the gut microbiota, promoting ISC maintenance in stress conditions through a metabolic loop involving fructose and glycolysis. 21 The novel approach of plasmid-mediated IL-22 delivery in second-generation probiotics has shown promise in preserving intestinal crypt stem cells and enhancing structural integrity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…18 Athiyyah's study showed that L. plantarum IS-10506 activates ISCs for inflammation mitigation, 19 while combined probiotic therapy has been effective in treating stomach erosions by modulating stem and secretory cell lineages. 20 Furthermore, dietary raffinose supports Lactobacillus reuteri in the gut microbiota, promoting ISC maintenance in stress conditions through a metabolic loop involving fructose and glycolysis. 21 The novel approach of plasmid-mediated IL-22 delivery in second-generation probiotics has shown promise in preserving intestinal crypt stem cells and enhancing structural integrity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A large number of speakers (12) and listeners (40) were united in the topic: «Clinical anatomy; morphological aspects of the somatic pathology; cell biology and biochemistry in the modern clinical research» (section 2).…”
mentioning
confidence: 99%